Design Of Illustrated Books Supporting Women's Programs To Strengthen The Identity And Thoughts Of Dewi Sartika - Rahmi, Lutfia Fatihah; Koesoemadinata, Mohammad Isa Pramana; Rahman, Yanuar (Sahabat Publikasi, 2025)
Dewi Sartika is an Indonesian educational figure who made a major contribution to advancing women's education in the early 20th century. The educational values she taught, such as life skills, are now starting to be forgotten in the modern education system, including at Dewi Sartika Elementary and Junior High Schools in Bandung. Based on the analysis of school conditions, it was identified that the lack of implementation of Dewi Sartika's values had an impact on the weak identity of the school. This study aims to design an illustration book as a companion to the craft-based mini course program to preserve Dewi Sartika's educational values and increase the program's appeal. This Illustration Book Supporting the “Keputrian” Program is designed with a focus on craft materials, such as hot press techniques to process plastic into new products, adopting visual narratives that are relevant to the learning styles of the younger generation. The design thinking approach is used to ensure that the designed solutions are able to meet the needs of users, namely students, teachers, and tourists. By combining elements of aesthetics, ergonomics, and Sundanese culture, this book is expected to be an effective, interesting, and inspiring educational media for readers. This design not only supports the preservation of traditional aspects and skills, but also supports the achievement of sustainable development goals (SDGS), especially in quality education and gender equality.